Prevalence and Associated Factors for Depressive Symptomatology in Chinese Adults During COVID-19 Epidemic - Peng, Songxu; Lai, Xin; Du, Yukai; Li, Yuting; Tian, Kunming; Gan, Yong (Frontiers in Psychology, 2020)
Background: The novel coronavirus disease (COVID-19) has been rapidly transmitted worldwide, which contributed to various psychological problems (such as fear, depression, and anxiety) among the general population in China. The purpose of this study is to investigate the prevalence and associated factors of depressive symptoms among Chinese adults. Methods: A cross-sectional study of Chinese adults was conducted during February 17–29, 2020. Symptoms of depression were assessed using the Center for Epidemiologic Studies Depression scale (CES-D). Results: A total of 3,399 respondents were included in the analysis. It was observed that 14.2% (481/3,399) of the participants were screened positive for depressive symptoms. In multivariate logistic regression analysis, older age (OR = 0.98; 95% CI: 0.97–0.99), smoking (OR = 1.57; 95% CI: 1.10–2.26), self-rated health (good: OR = 0.49; 95% CI: 0.37–0.66; fairly: OR = 0.60; 95% CI: 0.45–0.80), having greater support scores (OR = 0.95; 95% CI: 0.94–0.96), knowledge about the main symptom of COVID-19 (very clearly: OR = 0.58; 95% CI: 0.42–0.79; relatively clearly: OR = 0.59; 95% CI: 0.44–0.79), and staying in Wuhan within three months before the outbreak of epidemic (OR = 1.78; 95% CI: 1.34–2.38) were associated with depressive symptoms. Conclusions: A considerable proportion of the general population in China had depressive symptoms during the COVID-19 epidemic. Routine screening and targeted interventions for depression are needed among high-risk depressed individuals during the COVID-19 epidemic.